Anti-Cartel Enforcement in Bangladesh: Challenges and Prospects from Asian Experience - Paul, Shuvadeep (Dhaka University Law Journal, 2025)
A competition-friendly environment is a must for steady economic growth, which is a driving force for developing countries such as Bangladesh. A cartel is a potential barrier to promoting consumer welfare and overall market development. Hence, competition law is vital in supervising the market with its anti-cartel enforcement policies. Since this is a global phenomenon, countries have experimented and taken different strategies to combat cartels in their jurisdiction accordingly. Being a young competition jurisdiction, Bangladesh has a simple enforcement policy restricted to fines, but the cartel detection rate is quite unsatisfactory. This article aims to find the loopholes for anti-cartel enforcement in Bangladesh. It looks for a sustainable solution, especially introducing dawn raids, leniency mechanisms, and some other structural modifications, taking inspiration from global practices to address cartels in the Bangladeshi market. Dhaka University Law Journal, 2025, 36 (1), 193-207